2016
DOI: 10.1016/j.cub.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-7b Promotes Distal Tip Localization of the Intermicrovillar Adhesion Complex

Abstract: SUMMARY Transporting epithelial cells interact with the luminal environment using a tightly packed array of microvilli known as the ‘brush border’. During intestinal epithelial differentiation, microvillar packing and organization are driven by cadherin-dependent adhesion complexes, which localize to the distal tips of microvilli where they drive physical interactions between neighboring protrusions. Although enrichment of the “intermicrovillar adhesion complex” (IMAC) at distal tips is required for proper fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(97 citation statements)
references
References 49 publications
6
90
0
Order By: Relevance
“…Moreover, while all of these studies implicate motor activity in tip targeting of tandem MyTH4-FERM myosins, they do not rule out a role in cargo anchoring or retention. These more passive mechanisms find some support in recent studies on Myo7b, which demonstrated that a mutant predicted to exhibit defects in force generation was able to target to microvillar tips and partially rescue enrichment of specific cargoes [33 •• ]. However, even in that case, normal motor activity was required for full rescue of cargo enrichment and downstream functions [33 •• ].…”
Section: Movement and Localization Of Myth4-ferm Myosins In Protrusionsmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, while all of these studies implicate motor activity in tip targeting of tandem MyTH4-FERM myosins, they do not rule out a role in cargo anchoring or retention. These more passive mechanisms find some support in recent studies on Myo7b, which demonstrated that a mutant predicted to exhibit defects in force generation was able to target to microvillar tips and partially rescue enrichment of specific cargoes [33 •• ]. However, even in that case, normal motor activity was required for full rescue of cargo enrichment and downstream functions [33 •• ].…”
Section: Movement and Localization Of Myth4-ferm Myosins In Protrusionsmentioning
confidence: 85%
“…Myo15a and Myo7b target to the distal tips of stereocilia and microvilli, respectively, while Myo7a localizes to the upper tip-link density and ankle links of stereocilia [3133 •• ]. Although monomeric head-neck constructs that lack cargo-binding domains are unable to tip target, forced dimers of Myo7a and Myo7b motor domains do exhibit tip localization in filopodia and microvilli, respectively, demonstrating the potential for processive movement when multimerized [9 • ,33 •• ,34]. Motor activity is required for tip enrichment, further suggesting that this is an active process [33 •• ,34].…”
Section: Movement and Localization Of Myth4-ferm Myosins In Protrusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we used CACO-2 BBE cells to evaluate the role of Myo7b/USH1C binding in IMAC function and brush border assembly. Our previous studies showed that knockdown (KD) of Myo7b in CACO-2 BBE impairs IMAC formation, as shown by loss of IMAC component (USH1C, CDHR2 and CDHR5) enrichment at microvillar tips; these phenotypes were rescued by reexpression of WT Myo7b (37). We used a similar KD/rescue approach to evaluate the function of several mutants of Myo7b defective in USH1C PDZ3 binding (K1918E and R1921E in Myo7b CMF as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting images were used to calculate Pearson's correlation coefficient to examine the extent of colocalization between Myo7b constructs and USH1C or CDHR2 in microvilli. As a readout for IMAC function, we also visually scored the fraction of cells that exhibit robust microvillar clustering, as previously described (37). As a positive control, we reexpressed EGFP-tagged WT full-length Myo7b, which strongly colocalized with USH1C ( Fig.…”
Section: Resultsmentioning
confidence: 99%